Consideration of a New Form of Hydrolysed Beef Powder as a Source of High-Quality Protein for Elderly. [Consideraciones Sobre un Nuevo Hidrolizado en Polvo Extraído desde la Carne de Vacuno Como fuente de Proteínas de Alta Calidad para los Ancianos]. - Fernando Naclerio (Ramón Cantó Alcaraz, 2019)
An active lifestyle together with optimal nutrition is essential for preserving independent living and quality of life as people ageing. The minimum recommended daily intake for protein (0.8 g/kg) has been considered insufficient for supporting muscle growth and development in young and maintaining muscle mass in adults. Particularly older adults need a higher amount of daily protein intake (~1.0 to 1.2 g/kg or higher in more active elderly people) for maintaining muscle health because of the "anabolic resistance condition" in aged muscle. The quality of protein is essential to promoting muscle mass accretion and health. Beef is a high-quality protein source rich in essential amino acids, essential, fatty acid and micronutrients that is now available as a hydrolysed powder. Recent studies suggested the potential benefits of integrating this novelty form of beef into a regular diet for improving nutrition in athletes or elderly affected by the anabolic resistance condition or those suffering from difficulties in chewing or swallowing.